Las comunidades de práctica (CP): hacia una reconfiguración hermenéutica - Diego Fernando Barragán Giraldo (Franciscanum, 2015)
This article presents some insights on the concept «Communities of Practice». This concept was first introduced in the business administration field but, taken to the social sciences research one it can open up new opportunities of meaning and relevance. In the first part of the article, some methodological aspects are considered taking into account a current research project in which we have built up a Community of Practice where the theoretical framework could emerge. The second part, shows some insights on the «Communities of practice» concept, first by showing the genesis of the phenomenon in the interactions among the business administration field. Then, some of the singularities of the concept are presented taking it as something beyond the techniques in a clear dialogue with the hermeneutical philosophy. Finally, as a conclusion, a path for the social sciences research field using the Communities of Practice approach is proposed.